Живая планета: [океаны, пустыни, тропики, заполярье] / П. Беннет - Беннет Пол (Энциклопедия, 2008)
- Указ. : с. 126-128 5-6 кл. Экземпляры: ч/з ЦБ (2009) / Инвентарный номер: 65 / Сис.шифр: 26.82 / Авт.знак: Б46 / ББК: 26.82